Brugada syndrome update - Xu, Tingting; Wang, Shaokun; Wang, Jiawen; Xing, Jihong (Frontiers in Physiology, 2025)
Brugada syndrome (BrS), a genetic disorder affecting cardiac ion channels, predominantly manifests due to mutations that impair the function of the Nav1.5 sodium channel’s α-subunit. This condition, identified by Josep and Pedro Brugada, is often marked by symptoms such as syncope and episodes of polymorphic ventricular tachycardia (PVT) or ventricular fibrillation (VF). These arrhythmias, if not managed promptly, can escalate to sudden cardiac death (SCD), notably in patients whose cardiac structure appears normal. Given this, the prompt recognition and stratification of individuals at elevated risk are critical. This review elaborates on the current insights into BrS, focusing on recent diagnostic techniques, risk assessment strategies, and therapeutic advancements. It also critically examines ongoing controversies in the field.